Personalization of thoracoabdominal CT examinations using scanner integrated clinical decision support systems – Impact on the acquisition technique, scan range, and reconstruction type - Daniel, Sascha; Kopp, Markus; Vollbrecht, Thomas; Zeilinger, Martin; Fitz, Tim; Muttke, Armin; Feuerlein, Ute; Uder, Michael; May, Matthias (European Journal of Radiology, 2023)
Objectives: This study evaluates the impact of a scanner-integrated, customized clinical decision support system (CDSS) on the acquisition technique, scan range, and reconstruction in thoracoabdominal CT. Materials and Methods: We applied CDSS in contrast–enhanced examinations of the trunk with various clinical indications on a recent scanner with the capability of dual-energy CT (DECT), anatomic landmark detection (ALD), and iterative metal-artifact reduction (MAR). Simple and comprehensive questions about the patient's breath hold capability, the anatomical region of interest, and metal implants can be answered after the localizer. The acquisition technique (single energy, SECT, or dual energy), scan range (chest-abdomen-pelvis or chest-abdomen), and reconstruction technique (with or without MAR) were then automatically adapted in the examination protocols in coherence with these selections. Retrospectively, we compared the usage rates for these techniques in 624 examinations on the study scanner with 740 examinations on a comparable scanner without CDSS. Subgroup analysis of effective dose (ED), scan duration, and image quality (IQ) was performed in the study group. Results: CDSS leads to an increased usage rate of DECT (64.4% vs. 2.8%) and MAR (75.4% vs. 44.0%). All scan range adaptations by ALD were successful. The resulting subjective IQ between single energy and DECT acquisitions was comparable (all p > 0.05). Scan duration was significantly longer in DECT than in SECT (16.9 s vs. 6.5 s; p < 0.001). However, the objective IQ was significantly higher in DECT (CNRD 2.1 vs. 1.8; p < 0.01), and the ED significantly lower (6.7 mSv vs. 7.6 mSv; p = 0.004). Conclusion: CDSS for thoracoabdominal CT leads to a substantially increased usage rate of innovative techniques during acquisition and reconstruction. Patients with adapted protocols benefit from improved image quality and increased post-processing options at lower radiation doses.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Clinical decision support systems; CT; Dual-energy; Metal artifact reduction; Radiation dose